Design and computer construction of structural sleeve forms for women’s clothing - Marjanović, Jelena (Array, 2019)
The paper presents the research of the development process of a unique women’s clothing collection with complex, structural sleeve forms. Using the 2D/3D CAD systems for computer clothing design, 15 models of women’s clothing with structural sleeve forms were constructed and modeled. Textile patterns were also computer-designed, as a preparation for digital printing on cutting parts of a particular clothing models. The computer clothing design included all the segments of the computer 3D prototype development, with the purpose of investigating the possibilities of modeling and 3D simulations of complex sleeve structures, which in the real manufacturing process require additional fixation of cutting parts. The influence of 3D simulation parameters, in correlation with the applied physical and mechanical properties of textile material, was investigated in order to achieve complex 3D forms of simulated clothing models. Color and textile patterns variations of computer-designed 3D models were developed with the purpose of achieving a realistic visualization of the designed clothing collection. Original prototypes were made for two selected models from the collection, with computer-designed textile patterns applied on a model using digital printing technology.